Effects of climate change on high Alpine mountain environments: Evolution of mountaineering routes in the Mont Blanc massif (Western Alps) over half a century. Issue 1 (1st January 2019) - Mourey, Jacques; Marcuzzi, Mélanie; Ravanel, Ludovic; Pallandre, François
ABSTRACT: In high alpine environments, glacial shrinkage and permafrost warming due to climate change have significant consequences on mountaineering routes. Few research projects have studied the relationship between climate change and mountaineering; this study attempts to characterize and explain the evolution over the past 40 years of the routes described in The Mont Blanc Massif: The 100 Finest Routes, Gaston Rébuffat's emblematic guidebook, published in 1973.The main elements studied were the geomorphic and cryospheric changes at work and their impacts on the itinerary's climbing parameters, determining the manner and possibility for an itinerary to be climbed. Thirty-one interviews, and comparison with other guidebooks, led to the identification of 25 geomorphic and cryospheric changes related to climate change that are affecting mountaineering itineraries. On average, an itinerary has been affected by nine changes. Among the 95 itineraries studied, 93 have been affected by the effects of climate change – 26 of them have been greatly affected; and three no longer exist. Moreover, periods during which these itineraries can be climbed in good conditions in summer have tended to become less predictable and periods of optimal conditions have shifted toward spring and fall, because the itineraries have become more dangerous and technically more challenging.